العقدة الدرقيَّة العلاقة بين ( الجنس _ العمر _ الحجم ) والخباثة - علوش علي; أحمد عيسى; نوح فادي (Latakia University Journal -Medical Sciences Series, 2016)
اشتملت الدراسة على 156 مريضًا لديهم عقد درقية ,راجعوا قسم الجراحة في مشفى الأسد الجامعي باللاذقية بين عامي 2008 – 2012 . شكلت الإناث غالبية مرضى العقد الدرقية 133 مريضة أي بنسبة (85.26%) مقابل 23 مريضا (14.74%). معظم المرضى من الشباب وقمة الإصابة في العقد الرابع من العمر.كانت الشكاية الرئيسة لمعظم المرضى هي الضخامة في مقدمة العنق (78.21%).أجري الفحص السريري والإيكوغرافي لجميع المرضى وكان الفحص السريري هو مفتاح التشخيص لكن الإيكوغرافي كان أكثر دقة وأكثر مصداقية .أجريت الخزعة بالإبرة الرفيعة عند 30 مريضا وكانت موجهة عند 18 مريضا أما باقي الحالات فكانت سلبية النتيجة . أجريت الدراسة النسيجية لجميع العينات التي أخذت أثناء الجراحة وكانت بالنتيجة معظم العقد حميدة حيث شخصت الخباثة ل 23 مريضا فقط أي بنسبة 14.74%ومعظم هذه الخباثات كانت عبارة عن سرطان حليمي . بعد دراسة التوزع الجنسي والعمري للخباثة ومقارنتها مع التوزع الجنسي والعمري للعقد الدرقية تبين أن العقدة الدرقية لدى المريض الذكر تحمل خطورة أكبر لأن تكون خبيثة بنسبة (2:1) ,كذلك فإن نسبة العقدة الدرقية الخبيثة تزداد مع تقدم العمر, ولم توجد أي علاقة بين حجم العقدة الدرقية وخباثتها. The study concluded 156 patients having thyroid nodes. All the patients checked up in Assad university hospital in Lattakia between 2008-2012. The majority of patients having thyroid nodes were 133 females a 85,26% compared to 23 male patients a 14,74%. Most patients are young approximatelyin their forties’. 78,21% of patients complained about having an enormity in the upper side of their necks. All clinical and Ultrasound examinations were conducted on all patients. The clinical examination was the answer to diagnosis. From the other hand the Ultrasound examination was more accurate and reliable. Fine-Needle Aspiration (FNA) was done for 30 patients and it was directed to 18 patients, but the result was negative for the rest. All tissue samples, which were taken while surgery, were studied and the result was , most nodes were not tumors, as tumors were only discovered in 23 patients a 14,74% and the majority of those tumors were papillary carcinoma. The study concluded that thyroid node in male patients has a higher chance to be a tumor by (2:1),after studying the tumors spread according to age and sex factors compared to the spread of thyroid node according to the same factors. In addition,the study concluded that the possibility of having thyroid nodesbecomes bigger as one gets older.Ther is no relation between the size of thyroid node and it’s malignancy.